MARKETING AUTOMATION THROUGH EMAIL, DIGITAL ADVERTISING, AND SOCIAL MEDIA MANAGEMENT TO IMPROVE OPERATIONAL EFFICIENCY AND SCALABILITY OF MARKETING STRATEGIES IN THE DIGITAL AGE - Rudianto Rudianto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study examines the role of marketing automation through email, digital advertising, and social media management in improving operational efficiency and the scalability of marketing strategies in the digital age. Through a systematic literature review, the study examines various concepts, technologies, and the impact of automation implementation in these three marketing channels. The results of the study show that marketing automation can reduce manual workloads, accelerate marketing processes, improve the personalisation of customer communications, and enable broader market expansion through the efficient use of resources. The integration of automation in email, digital advertising, and social media also creates synergies that strengthen the consistency and effectiveness of digital marketing strategies. The practical implications of this research provide recommendations for businesses to utilise marketing automation as a strategic tool in facing the challenges and opportunities of business competition in a dynamic digital era.